MEMAHAMI PRAKTEK PRODUKSI AUDIO ORANG DENGAN GANGGUAN PENGLIHATAN - Chitra Lestari, S.I.Kom, M.I.Kom, Chitra Lestari, S.I.Kom, M.I.Kom (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2023)
The advent of digital audio workstations and other digital audio tools has brought about a notable change in the audio industry by empowering both amateur and professional audio content creators with the tools necessary to produce high-quality audio content. However, we know very little about the accessibility of audio production tools that are widely used for the visually impaired. Through interviews with 18 audio professionals and the visually impaired hobbyist, we found that accessible audio production involves: putting together accessible and efficient workflows through a combination of key and specialized tools; achieve professional competency through a steep learning curve where domain knowledge and accessibility are inseparable; and facilitating learning and creating access by engaging in an online community of visually impaired audio enthusiasts. We discuss the deep link between accessibility and professional competence and end with design considerations to inform the development of future accessible audio production tools.